Physicochemical Properties, Biological Activity, Health Benefits, and General Limitations of Aged Black Garlic: A Review - Ryu, Ji Hyeon (Molecules, 2017)
Garlic (Allium sativum) has been used as a medicinal food since ancient times. However, some people are reluctant to ingest raw garlic due to its unpleasant odor and taste. Therefore, many types of garlic preparations have been developed to reduce these attributes without losing biological functions. Aged black garlic (ABG) is a garlic preparation with a sweet and sour taste and no strong odor. It has recently been introduced to Asian markets as a functional food. Extensive in vitro and in vivo studies have demonstrated that ABG has a variety of biological functions such as antioxidant, anti-inflammatory, anti-cancer, anti-obesity, anti-diabetic, anti-allergic, cardioprotective, and hepatoprotective effects. Recent studies have compared the biological activity and function of ABG to those of raw garlic. ABG shows lower anti-inflammatory, anti-coagulation, immunomodulatory, and anti-allergic effects compared to raw garlic. This paper reviews the physicochemical properties, biological activity, health benefits, adverse effects, and general limitations of ABG.